2020
DOI: 10.3390/ijerph17165681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liquefied Petroleum Gas Cookstoves and Wood Cooking Fires on PM2.5 Trends in Brick Workers’ Homes in Nepal

Abstract: Prior studies document a high prevalence of respiratory symptoms among brick workers in Nepal, which may be partially caused by non-occupational exposure to fine particulate matter (PM2.5) from cooking. In this study, we compared PM2.5 levels and 24 h trends in brick workers’ homes that used wood or liquefied petroleum gas (LPG) cooking fuel. PM2.5 filter-based and real-time nephelometer data were collected for approximately 24 h in homes and outdoors. PM2.5 was significantly associated with fuel type and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Previous studies by our group found that Nepali brick workers, in addition to having hazardous work-related respiratory exposures [20], experience significant PM 2.5 exposures during non-working hours [18,19]. Indoor PM 2.5 concentrations in brick workers' homes with wood fire and LPG cookstoves were 541.14 and 79.32 µg/m 3 , respectively, and these elevated levels coincided with meal and sleep times [19].…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Previous studies by our group found that Nepali brick workers, in addition to having hazardous work-related respiratory exposures [20], experience significant PM 2.5 exposures during non-working hours [18,19]. Indoor PM 2.5 concentrations in brick workers' homes with wood fire and LPG cookstoves were 541.14 and 79.32 µg/m 3 , respectively, and these elevated levels coincided with meal and sleep times [19].…”
Section: Introductionmentioning
confidence: 78%
“…We collected PM 2.5 samples using both filter-based and real-time nephelometer methods. Our previous study reported the PM 2.5 total mass and nephelometer trend analyses [19]. For this study, we analyzed the 25 mm 3.0 µm PTFE filters (Zefon International, Ocala, FL, USA) for 35 chemical constituents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations